An Overview of Indonesian Renewable Energy Studies and Its Investment Opportunities - Alfred Boediman; Raden Aswin Rahadi; Bagus Aditya Nugraha (Purnomo Yusgiantoro Center, 2021)
By conducting a synthesis review of recent literature, this study aims to provide a comprehensive conceptual model for acknowledging factors determining private investment in the renewable energy sector within an emerging country, Indonesia. The synthesis and thus guides stakeholders to encourage investment from the private sector in renewable energy development. From this study, the authors summarized all factors studied arguably influential in affecting the private sector to invest as a source of development funding and presenting several key indicators of renewable energy investment opportunities in Indonesia. The factors that influence the development of the energy sector include policies related to human capital, environmental protection and energy efficiency. Therefore, this study should serve as the baseline for future advanced studies. Keywords: renewable energy, investment opportunities, emerging country, Indonesia